The role of foreign direct investment in the transfer and localization of information technology, a case study in Lafarge M’sila Ciment Company - Herouz Khelifa; Mohamed laid Khatim (My University, 2022)
This study aims to learn about the role of FDI in the transfer and localization of information technology from the point of view of a sample of lafarge liquefied cement workers, and to achieve This was developed a model consisting of an independent FDI variable and an IT variable through its five dimensions (physical components, software, databases, communication networks and individuals), and the descriptive approach and data collection from the sample vocabulary were developed through the form as an essential tool from the study sample, which includes the help of the study sample, which includes the help of And the 88 workers from a community of 464 workers. After testing the theories of the study through the method of association and regression, a correlation and impact between the two variables were found in the company in question, and the researchers made a set of recommendations
Keywords: foreign direct investment, information technology, information technology components